Analisis Densitas Bentik Dinoflagellata Gambierdiscus, Ostreopsis dan Prorocentrum di Pantai Nirwana, Padang - Thamrin Thamrin,M.Sc (Dinamika Lingkungan Indonesia, 2020)
Environmental degradation has occurred in various ecosystems in the world. This  also carries out in the sea and even sometimes threaten human life, whether directly or indirectly. Likewise, events in the marine environment associated with poisoning, caused by toxic algae such as dinoflagellates. To see the progress the survey research was conducted on Thallasia sp to see the growth of toxic dinoflagellates Gambierdiscus, Ostreopsis and Prorocentrum in the Nirwana Coast Padang. The data analysis uses two-way statistics with Turkey's Advanced Test. The results showed that Gambierdiscus and Ostreopsis almost the same number and were still low. High striking results occurred on Prorocentrum which differed markedly from both Gambierdiscus and Ostreopsis. This results also significantly different among stations.